2018
DOI: 10.1007/s10482-018-1147-0
|View full text |Cite
|
Sign up to set email alerts
|

The plant-growth-promoting actinobacteria of the genus Nocardia induces root nodule formation in Casuarina glauca

Abstract: Actinorhizal plants form a symbiotic association with the nitrogen-fixing actinobacteria Frankia. These plants have important economic and ecological benefits including land reclamation, soil stabilization, and reforestation. Recently, many non-Frankia actinobacteria have been isolated from actinorhizal root nodules suggesting that they might contribute to nodulation. Two Nocardia strains, BMG51109 and BMG111209, were isolated from Casuarina glauca nodules, and they induced root nodule-like structures in origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Besides, there were other genera such as Actinomadura, Microbiospora, Micromonospora and Nocardia also shared in two or three C. oleifera samples. Studies have reported that these actinobacterial genera showed potential for use as biofertilizers in other crops including chickpea [56], alfalfa [57], Casuarina glauca [58]. These suggested that the endophytic actinobacteria from C. oleifera possessed wide range of application and great development value.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there were other genera such as Actinomadura, Microbiospora, Micromonospora and Nocardia also shared in two or three C. oleifera samples. Studies have reported that these actinobacterial genera showed potential for use as biofertilizers in other crops including chickpea [56], alfalfa [57], Casuarina glauca [58]. These suggested that the endophytic actinobacteria from C. oleifera possessed wide range of application and great development value.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these isolates were ignored or discarded as being irrelevant to the plants. However, these non- Frankia Actinobacteria have consistently been isolated from several actinorhizal plants including Casuarina ( Guillén et al, 1993 ; Niner et al, 1996 ; Valdes et al, 2005 ; Ghodhbane-Gtari et al, 2010 ), and consist of Actinobacteria from Micromonospora ( Valdes et al, 2005 ; Ghodhbane-Gtari et al, 2010 ), Nocardia ( Ghodhbane-Gtari et al, 2010 , 2019 ) and Streptomyces genera ( Ghodhbane-Gtari et al, 2010 ). Similarly, non-symbiotic bacteria, such as Azospirillum , Bacillus , Pseudomonas , and Streptomyces , are known to be auxiliary bacteria in several Rhizobium -legume symbioses ( Iruthayathas et al, 1983 ; Grimes and Mount, 1984 ; Li and Alexander, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three 2-month-old Casuarina glauca plants were inoculated with 2 ml of a concentrated culture of F. casuarinae strain CcI3(pHKT1) transformant. After 2 months incubation, an average of 35 nodules per plant were collected and sterilized (41). After a week of incubation in LB medium, 6 nodules were crushed with a sterile mortar.…”
Section: Methodsmentioning
confidence: 99%